Function of the pseudo phosphotransfer proteins has diverged between rice and Arabidopsis. (8th February 2021) - Vaughan‐Hirsch, John; Tallerday, Emily J.; Burr, Christian A.; Hodgens, Charlie; Boeshore, Samantha L.; Beaver, Kevin; Melling, Allison; Sari, Kartika; Kerr, Ian D.; Šimura, Jan; Ljung, Karin; Xu, Dawei; et al.
SUMMARY: The phytohormone cytokinin plays a significant role in nearly all aspects of plant growth and development. Cytokinin signaling has primarily been studied in the dicot model Arabidopsis, with relatively little work done in monocots, which include rice ( Oryza sativa ) and other cereals of agronomic importance. The cytokinin signaling pathway is a phosphorelay comprised of the histidine kinase receptors, the authentic histidine phosphotransfer proteins (AHPs) and type‐B response regulators (RRs). Two negative regulators of cytokinin signaling have been identified: the type‐A RRs, which are cytokinin primary response genes, and the pseudo histidine phosphotransfer proteins (PHPs), which lack the His residue required for phosphorelay. Here, we describe the role of the rice PHP genes. Phylogenic analysis indicates that the PHPs are generally first found in the genomes of gymnosperms and that they arose independently in monocots and dicots. Consistent with this, the three rice PHPs fail to complement an Arabidopsis php mutant ( aphp1/ahp6 ). Disruption of the three rice PHPs results in a molecular phenotype consistent with these elements acting as negative regulators of cytokinin signaling, including the induction of a number of type‐A RR and cytokinin oxidase genes. The triple php mutant affects multiple aspects of rice growth and development, including shoot morphology, panicle architecture, and seed fill. In contrast to Arabidopsis, disruption of the rice PHPs does not affect root vascular patterning, suggesting that while many aspects of key signaling networks are conserved between monocots and dicots, the roles of at least some cytokinin signaling elements are distinct. Significance Statement: We demonstrate that the function of the rice pseudo histidine phosphotransfer proteins has diverged from their Arabidopsis counterparts, despite data indicating that these rice proteins are also negative regulators of cytokinin signaling.